Technologizing Bronfenbrenner: Neo-ecological Theory - Navarro, Jessica L.; Tudge, Jonathan R. H. (Current psychology (New Brunswick, N.J.), 2023)
We propose an adaptation of Urie Bronfenbrenner’s bioecological theory, neo-ecological theory . As bioecological theory was developed in the 20 th century, it requires significant modifications to reflect some of the most ubiquitous contexts in which adolescents learn, play, and grow—the technological and virtual ones. Although several scholars have developed laudable theories related to youth development in virtual contexts, the field lacks an overarching theory to address the intersection of development and technology. In developing neo-ecological theory, we hold true to the tenets of bioecological theory, but suggest key modifications to reflect our technologized world. We delineate a key alteration to the microsystem, namely the existence of two types of microsystems—physical and virtual. In addition, we emphasize the importance of macrosystemic influences (i.e., the influences of culture and within-society subcultural variation) in understanding development in the digital age. The implications of these modifications cascade across the Process-Person-Context-Time (PPCT) model; proximal processes, person characteristics, context, and time are all reexamined. In the digital age, virtual microsystems are central contexts in which youth engage in proximal processes. As such, we believe that all scholars of development, regardless of their specific research interests, should consider the ways digital contexts influence their outcomes of interest. Without it, practitioners, policy makers, parents, and technologists will be in the dark about how best to support adolescents.